Delivering the discipline: Teaching geography and planning during COVID‐19. (13th April 2021) - Fuller, Sara; Ruming, Kristian; Burridge, Andrew; Carter‐White, Richard; Houston, Donna; Kelly, Linda; Lloyd, Kate; McGregor, Andrew; McLean, Jessica; Miller, Fiona; O'Gorman, Emily; Suchet‐Pearson, Sandie; et al.
Abstract: COVID‐19 has radically changed the higher education sector in Australia and beyond. Restrictions on student movement (especially for international students) and on gatherings (which limited on‐campus sessions) saw universities transition to fully online teaching modes almost overnight. In this commentary, we reflect on this transition and consider the implications for teaching the disciplines of geography and planning. Reflecting on experiences at the Department of Geography and Planning at Macquarie University, we explore a series of challenges, responses and opportunities for teaching core disciplinary skills and knowledge across three COVID‐19 moments: transition, advocacy, and hybridity. Our focus is on the teaching of core disciplinary skills and knowledge and specifically on geographical theory, methods, and fieldwork and professional practice skills. In drawing on this case from Macquarie University, we offer insights for the future of teaching geography and planning in universities more broadly.